(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The presentation of beauty in English and Ukrainian proverbs has been determined. It has been demonstrated that the concept of Beauty is the expression of ethnic culture and the main unit of linguistic consciousness. The attitudinal meaning of the declared concept is closely connected with the value navigators of the society behavior. It has been proved that common presentation of beauty in English and Ukrainian paremiologia tends towards opposition of inner beauty and man’s appearance.